Negotiating Feelings and Multiculturalism:Towards a Sociological Study on Cultural Shock and Intercultural Communication - Zinia, Josinta; Zinia, Josinta; Sultana, Tahmina; Mahmud, Muhammad Kawsar (Advances in Social Sciences Research Journal, 2018)
Cultural shock is an anxiety produced when a person moves from a familiar culture to an entirely different cultural or social environment. This paper is an attempt to describe how Bangladeshi students experience cultural shock while studying in different foreign universities. The main purpose of this study is to examine perceptions of cultural shocks among the Bangladeshi students and its psychological impact on them. This study follows quantitative research methodology. This study reveals that there is a considerable cultural shock exists among the students staying abroad. These shocks include but not limited to food complicacy, financial intricacy, environmental complexity, a new pattern of dress-up, and language barrier.